2022
DOI: 10.1002/kjm2.12554
|View full text |Cite
|
Sign up to set email alerts
|

A review of the phytochemical and pharmacological properties ofAmauroderma rugosum

Abstract: Amauroderma rugosum (AR) is a basidiomycete in the Ganodermataceae family that has been used traditionally to prevent epileptic attacks and constant crying in babies. However, AR has not been widely studied scientifically. In this review, we summarize the phytochemical components and pharmacological properties of AR that have been reported in the literature. Chemical analyses have revealed that the components of AR include sterols, flavonoids, fatty acids and esters, aromatic acids and esters, phenols, polysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…It has been suggested that AR possesses anti-inflammatory properties. In Asian countries, such as China, AR is used as a medicinal herb for the treatment of acute or chronic nephritis [ 9 ]. Moreover, an in vitro study has reported that AR can reduce the gene expression of TNF-α in RAW264.7 cells [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that AR possesses anti-inflammatory properties. In Asian countries, such as China, AR is used as a medicinal herb for the treatment of acute or chronic nephritis [ 9 ]. Moreover, an in vitro study has reported that AR can reduce the gene expression of TNF-α in RAW264.7 cells [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant compounds have been widely proposed for the prevention of various skin disorders [ 27 , 28 ]. Antioxidant effect is the most reported bioactivity of AR [ 9 ]. Consistently, the present study also demonstrated the antioxidant effects of AR aqueous extract in HaCaT keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Several Ganodermataceae species, such as G. amboinense, G. australe, G. applanatum, G. lucidum, G. lingzhi, G. sinense, G. tsugae, and A. rugosum, have been cultured to collect polysaccharides from the mycelia. [6][7][8][9][10][11] A. subresinosum is a species belonging to the Amauroderma genus in the Ganodermataceae family, which is classified under the Polyporales order. It is commonly found in tropical regions.…”
Section: Introductionmentioning
confidence: 99%